INFLUENCE OF PHYSIOLOGICAL PARAMETERS AND YIELD BY DIFFERENT MAIZE BASED CROPPING SYSTEM - A. K. JHA; SONAM SHRI; ARTI SHIRVASTAVA (The Bioscan, 2015)
A field experiment was conducted during Kharif season 2011 under All India Co-ordinated Research Project on Forage Crop at Farm of Agriculture College, Jabalpur to study the “Resource utilization in fodder maize based- intercropping system”. Sole maize resulted in highest seed yield (18.53 q/ha) and stover yield (150.37 q/ha). Among the intercropping systems maize + soybean was found better. The intercropping of maize with soybean, ricebean and cowpea with 1:1 and 1:2 ratios gave maximum maize equivalent yield than sole crop. The intercropping of maize with soybean 1:2 ratio posses the maximum energy interception (0.85), energy utilization (3.63), PAR interception (1104.11), PAR utilization (2100) and also gave the maximum LER 1.57 than sole maize.